Interaction picture density matrix quantum Monte Carlo - Malone,FD; Blunt,NS; Shepherd,JJ; Lee,DKK; Spencer,JS; Foulkes,WMC (Journal of Chemical Physics, 2015)
The recently developed density matrix quantum Monte Carlo (DMQMC) algorithm stochastically samplesthe N-body thermal density matrix and hence provides access to exact properties of many-particle quantumsystems at arbitrary temperatures. We demonstrate that moving to the interaction picture provides substan-tial benefits when applying DMQMC to interacting fermions. In this first study, we focus on a system ofmuch recent interest: the uniform electron gas in the warm dense regime. The basis set incompleteness errorat finite temperature is investigated and extrapolated via a simple Monte Carlo sampling procedure. Finally,we provide benchmark calculations for a four-electron system, comparing our results to previous work wherepossible.